Sosialisasi Pengendalian Kualitas Pelayanan Guna Meningkatkan Kepuasan Pelanggan Pada UD. Putra Azzam Service - Rizqy Cahya Putra Fil Akbar; Moh. Jufriyanto; Yanuar Pandu Negoro (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Business competition is everywhere. Not only in production, but also in service. UD. Putra Azzam Service is a company engaged in computer service and installation. Partners always strive to provide the best service that their customers want and try to improve their competitiveness. From observations through a survey of partner owners, it was found that there were several customer complaints related to damage to goods after purchase or other problems that arose after service. The effect is a decrease in customers in February – April 2021. Servqual and Quality Function Deployment (QFD) methods can be used to find ways to improve service to partners. This community service activity is intended for that. Activities are carried out by observing the service process, obtaining customer complaint data and analyzing the results to determine recommendations for corrective actions. These recommendations are conveyed to partners in dissemination activities. Partners welcome the suggestions given.